MANAJEMEN PEMBERDAYAAN DALAM PENINGKATAN MUTU PENDIDIKAN ISLAM DI INDONESIA - Fachruddin Fachruddin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2009)
The major problem of education in Indonesia is the low quality in any levels, kinds and units of education, such as pre-school, primary, secondary and higher education, including Islamic education. Data show that there was no significant changes in general though few schools and madrasahs show promising quality improvement. Some students from big cities in Indonesia were awarded medals in international Olympic. This article which is inspired by a seminar on management of empowerment in improving quality of education discusses the nature of such management, investigates various factors of involution in education, various efforts in reinventing education quality improvement and reconstruct management of empowerment for the future.